Role of adipose tissue in haemostasis, coagulation and fibrinolysis - Faber, D.R; de Groot, Ph.G; Visseren, F.L.J (Obesity reviews, 2009)
Obesity is associated with an increased incidence of insulin resistance (IR), type 2 diabetes mellitus and cardiovascular diseases. The increased risk for cardiovascular diseases could partly be caused by a prothrombotic state that exists because of abdominal obesity. Adipose tissue induces thrombocyte activation by the production of adipose tissue-derived hormones, often called adipokines, of which some such as leptin and adiponectin have been shown to directly interfere with platelet function. Increased adipose tissue mass induces IR and systemic low-grade inflammation, also affecting platelet function. It has been demonstrated that adipose tissue directly impairs fibrinolysis by the production of plasminogen activator inhibitor-1 and possibly thrombin-activatable fibrinolysis inhibitor. Adipose tissue may contribute to enhanced coagulation by direct tissue factor production, but hypercoagulability is likely to be primarily caused by affecting hepatic synthesis of the coagulation factors fibrinogen, factor VII, factor VIII and tissue factor, by releasing free fatty acids and pro-inflammatory cytokines (tumour necrosis factor-α, interleukin-1β and interleukin-6) into the portal circulation and by inducing hepatic IR. Adipose tissue dysfunction could thus play a causal role in the prothrombotic state observed in obesity, by directly and indirectly affecting haemostasis, coagulation and fibrinolysis.